Millennial-aged adults learning online: Factors impacting academic success - Sarah J Herchel (Adult Education Research Conference, 2016)
This quantitative study of 118 Millennial-aged learners enrolled in online courses administers a pre and post survey to measure self-directed learning readiness, academic achievement, and other factors related to these variables.
Keywords: self-directed learning; online contexts; millennial generation